Encyclopedia of global religion - Juergensmeyer, Mark.; Roof, Wade Clark (Thousand Oaks, Calif. : SAGE Publications, 2012)
Provides an overview of the globalization of religious culture and society around the world in its historical and contemporary aspects; includes topics related to the diaspora of cultures and dispersions of peoples; the transitional aspects of religious ideas and practices; the cultural diversity of religious traditions; the responses of religion--both negative and positive--to multicultural society; and essays on the contemporary religious society of every country in the world.
V. 1. A-L -- v. 2. M-Z, Index.
"A SAGE reference publication."
Includes bibliographical references and index.
Description based on print version record.
Keywords: Religions -- Encyclopedias; RELIGION / Reference; Electronic references sources; Electronic encyclopedias; Reference books; Electronic books